2015
DOI: 10.3109/11038128.2015.1095235
|View full text |Cite
|
Sign up to set email alerts
|

Choice and control for people ageing with intellectual disability in group homes

Abstract: Background Many people ageing with intellectual disabilities [ID] age in place in group homes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 42 publications
1
12
0
1
Order By: Relevance
“…This leads to increased reliance on supportive others when using ICTs and decreased opportunities to demonstrate choice and control over ICT use and related activities. In line with the work of Nader-Grosbois and Lefèvre (2012) and Kåhlin et al (2016), we note the importance of providing individualized support to individuals with ID, without imposing unnecessary control on how ICTs are used. Our findings highlight that digital inclusion for people with ID depends on the interaction between the opportunities provided within their social context and personal skills, as illustrated in Figure 1.…”
Section: Digital Inclusionsupporting
confidence: 83%
“…This leads to increased reliance on supportive others when using ICTs and decreased opportunities to demonstrate choice and control over ICT use and related activities. In line with the work of Nader-Grosbois and Lefèvre (2012) and Kåhlin et al (2016), we note the importance of providing individualized support to individuals with ID, without imposing unnecessary control on how ICTs are used. Our findings highlight that digital inclusion for people with ID depends on the interaction between the opportunities provided within their social context and personal skills, as illustrated in Figure 1.…”
Section: Digital Inclusionsupporting
confidence: 83%
“…One of the participants provided his/her personal observations of a lack of voice and choice people with ID have in group homes or alike facilities. This finding is supported by Kåhlin, Kjellberg, and Hagberg (2016), who conducted an ethnographic study of how choice and control of persons with ID is performed in the group homes. They concluded that ageing people with ID are vulnerable in regards to maintaining choice and control in group homes, and that choice-making and control are often restricted by staff members.…”
Section: Discussionmentioning
confidence: 69%
“…Our study shows that participants’ management of a broken agreement was characterized by negative emotions that were masked by maintaining a positive exterior and the participants’ positive view of the staff member and her conduct. The imbalance between the level of individual participant choice and staff control is influenced by the uniquely created environment that exists in the care of people with intellectual disabilities (e.g., Kåhlin, Kjellberg, & Hagberg, 2016). This imbalance was described in three themes: being emotionally touched , being aware of the other , and being unclear .…”
Section: Discussionmentioning
confidence: 99%